Internalisasi Nilai-nilai Al-Islam dan Kemuhammadiyahan Dalam Aktivitas Belajar - Nihayati Nihayati; Ogi Ponandi (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to describe the implementation of internalization of Islamic values in learn- ing activities in the Mathematics Education program FKIP University Of Muhammadiyah Pringsewu Lampung. The type of research is descriptive research, subject is lecturer of Mathematics Education program, data collection technique is observation and data anal- ysis using qualitative descriptive with percentage. The result of this research is the lecturer in internalizing the moral value of Allah SWT belongs to the category of Very Good and the lecturer in internalizing the personal morals including the Good category, with the process done through 3 stages: transformation stage, transaction and value transinternalisasi by using some techniques that is modeling, disciplinary coaching and motivation in learning activities.